Aesthetic Clothing in the Quran: Normative and Innovative Analysis - Agusriana, Sundari; Hakim, Lukman Nul; Ilyas, Deddy (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2024)
This study examines the notion of clothes as depicted in the Qur'an. This study is of considerable importance, particularly in light of contemporary societal conditions, which indicate that many Muslim women predominantly concentrate on the normative aspects of attire while seemingly neglecting its aesthetic dimensions. In fact, the aesthetic dimension is crucial in fostering a positive portrayal of Islam in the face of pervasive negative perceptions that are frequently linked to the manner and style of dress among Muslims. To explore this, the study undertakes a comprehensive literature review of Qur'anic texts pertaining to clothing, including terms such as hijab, khimar, and jilbab, using a thematic interpretative approach. The primary source is the Qur'an, complemented by secondary sources drawn from classical, modern, and contemporary scholars' interpretations, including Jilbab Baju Wanita Muslimah by Quraish Shihab and other pertinent literature. The data collected from these sources are further analysed through the lens of Fazlur Rahman’s double movement interpretative framework, which helps contextualise the Qur'anic teachings in relation to contemporary social and cultural contexts. The analysis shows that clothing in the Qur'an functions not just to cover the awrah (private parts) but also as a medium for expressing the beauty of Islam, both visually and in the interpretative value of its teachings. Therefore, in addition to its normative dimension, the Qur'an also emphasizes aesthetics. Muslims who adhere to the prescribed criteria of dress are encouraged to express their creativity in a refined and sophisticated manner, thereby reflecting Islam as a dynamic and adaptable religion in response to changing circumstances.